Potentiality of Cannabis as an Antibiotic (Antimicrobial) Agent - Rahadian, Wurgan (Buletin Farmatera, 2021)
Cannabis sativa, or widely known as ganja and other names in Indonesia, is a plant that could not be used in the health care system in Indonesia. It is because cannabis is still a Class 1 Narcotic. However, trends within the last few years show that cannabis has medicinal properties, and is already approved as medicine and (even) for recreational means in several nations/countriesThailand is the first nation in Southeast Asia that did. This article aims to emphasize the antimicrobial potential that cannabis has. Since conventional antibiotic is considered unable to provide, it is important to find another source to counter the high rates of antibiotic (antimicrobial) resistance. Moreover, this article is also aimed to introduce one of the potentials that cannabis have to Indonesia since scientific article written in Bahasa is rare.